Composition Dependence of Elastic Moduli of Mixed Cobalt-Zinc Ferrites Prepared by Citrate Precursor Method - Vinuthna, Ch.; Raju, Sandupatla; Ravinder, D. (Asian Journal of Chemistry, 2019)
CoxZn1-xFe2O4 nanoparticles were prepared by chemical citrate precursor synthesis method. The Young’s modulus ‘E’ and the rigidity modulus ‘n’ of mixed cobalt-zinc ferrites have been determined by the ultrasonic pulse transmission technique at 1 MHz. The elastic modules of the ferrites were corrected to zero porosity using the formulae of Harselman and Fulrath. The observed variation of the elastic module with composition has been interpreted on the basis of binding forces between the atoms of the spinal lattice. A linear relationship between Debye temperature ØD and average sound velocity Vm has also been observed.